Evaluasi Soundscape pada Taman Lalu Lintas sebagai Ruang Terbuka Edukatif dan Rekreatif Berkelanjutan - Fitriani, Fitriani; Astuti, Retno Fitri; Prasetyo, Sutrisno Aji; Herol, Herol (Universitas Pelita Bangsa, 2025)
The rapid population growth in the Greater Jakarta (Jabodetabek) region, including Bekasi, has increased traffic intensity and reduced the acoustic quality of public spaces. The Traffic Park in Kabupaten Bekasi serves a dual function as both an educational facility for children's traffic safety and a family recreational area. This study aims to evaluate the park’s soundscape quality using a mixed quantitative and qualitative approach. Sound Pressure Level (SPL) measurements were conducted with a Sound Level Meter at eight strategic points. In addition, sound recordings and open-ended interviews with 70 respondents were used to assess visitor perceptions. SPL data were compared to the Indonesian environmental noise standard (Kep-48/MENLH/11/1996), while perception data were analyzed descriptively. Results indicate that noise levels at the main entrance and roadside areas reach 72–78 dBA, exceeding the 55 dBA threshold. Anthropogenic sounds dominate the acoustic environment, whereas natural sounds (biophony and geophony) are only audible in the densely vegetated zones during morning hours. Most respondents (68%) perceive the roadside area as noisy, while 74% feel comfortable in the vegetated zones. Recommendations include adding noise-buffering vegetation, introducing water features, reorganizing activity zoning, and limiting the use of loudspeakers at kiosks. The soundscape approach is proven to provide a scientific basis for enhancing auditory comfort while strengthening the park’s educational function.